2007
DOI: 10.1038/sj.leu.2404594
|View full text |Cite
|
Sign up to set email alerts
|

High expression of several tyrosine kinases and activation of the PI3K/AKT pathway in mediastinal large B cell lymphoma reveals further similarities to Hodgkin lymphoma

Abstract: Mediastinal large B-cell (MBL) and classical Hodgkin lymphoma (HL) have several pathogenic mechanisms in common. As we recently observed aberrant tyrosine kinase (TK) activities in HL, we now analysed also MBL for such activities. Indeed, MBL and HL were the only B-cell lymphomas where elevated cellular phospho-tyrosine contents were typical features. Three TKs, JAK2, RON and TIE1, not expressed in normal B cells, were each expressed in about 30% of MBL cases, and 75% of cases expressed at least one of the TKs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 49 publications
1
26
0
1
Order By: Relevance
“…Considering that HRS cells are usually hyperploid, an estimation of the ploidy level was obtained as the mean value of copy numbers from 12 different loci (data not shown). 28,30 Copy numbers from FISH analyses of NOTCH1 and STAT6 were adjusted to the estimated ploidy levels of the cHL cases. The genomic status was then determined according to the following criteria: ratios of gene/ploidy level lower than 0.7 were considered as genomic loss, ratios between 0.7 and 1.3 as balanced, ratios higher than 1.3 and lower than 2 as genomic gains, and ratios above 2 as genomic amplifications.…”
Section: Fish and Fictionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that HRS cells are usually hyperploid, an estimation of the ploidy level was obtained as the mean value of copy numbers from 12 different loci (data not shown). 28,30 Copy numbers from FISH analyses of NOTCH1 and STAT6 were adjusted to the estimated ploidy levels of the cHL cases. The genomic status was then determined according to the following criteria: ratios of gene/ploidy level lower than 0.7 were considered as genomic loss, ratios between 0.7 and 1.3 as balanced, ratios higher than 1.3 and lower than 2 as genomic gains, and ratios above 2 as genomic amplifications.…”
Section: Fish and Fictionmentioning
confidence: 99%
“…The genomic status was then determined according to the following criteria: ratios of gene/ploidy level lower than 0.7 were considered as genomic loss, ratios between 0.7 and 1.3 as balanced, ratios higher than 1.3 and lower than 2 as genomic gains, and ratios above 2 as genomic amplifications. 28,30 For six of seven cHL cases studied for JUNB the ploidy levels were not available. In those cases, the JUNB genomic status was determined using the following criteria: signal copy numbers below 5 were defined as balanced (considering the characteristic tri-to tetraploidy of HRS cells), between 5 and 8 gained, and above 8 amplified.…”
Section: Fish and Fictionmentioning
confidence: 99%
“…19 Recent studies demonstrate that six RTKs, including RON, are expressed in Hodgkin/Reed-Sternberg HL cells and suggest that RON may be involved in the pathogenesis of HL. 20 Our results indicate that RON expression is significantly higher in BL and HL tissues than in normal lymph node and other lymphoma tissues. IHC staining showed that RON staining intensity and the number of positive cells are significantly higher in EBV + patients than in EBV -patients.…”
Section: Distribution and Expression Of Ron In Lymphomasmentioning
confidence: 54%
“…Thus, HRS cells express 8 RTKs, platelet-derived growth factor receptor (PDGFR) a, DDR2, EPHB1, RON, TRKA, TRKB, TIE1, and CSF1R, in varying patterns, and PDGFRa and TRKA have been shown to be activated in primary cases (5)(6)(7). As mutations affecting RTKs could not be detected in HRS cell lines and as activating ligands were frequently co-expressed in HRS cells or expressed by surrounding cells in the infiltrate of primary Hodgkin lymphoma cases (5), the receptors are presumed to be activated in an autocrine or paracrine fashion.…”
Section: Introductionmentioning
confidence: 99%